Culeolus likae Sanamyan K. & Sanamyan N. 2002 - Maggioni, Tamara; Rimondino, Clara; Taverna, Anabela; Reyna, Paola; Lagger, Cristian; Alurralde, Gastón; Calcagno, Emilia; Tatián, Marcos (Zenodo, 2022)
Culeolus likae Sanamyan K. & Sanamyan N., 2002 Figure 7 Culeolus likae Sanamyan K. & Sanamyan N. 2002: 347, fig. 26-27. Material examined : 70°40’S, 14°43’W, station 7, 3000 m, 22 Feb 2005, one specimen; 68°32’S, 20°24’W, station 9, 4930 m, 27 Feb 2005, one specimen. Description. Both specimens have a similar external aspect (Fig. 7A). The smaller specimen is 4 cm long and 1.7 cm wide, while its peduncle reaches 15 cm in length. The larger specimen is 10.9 cm long and 5.2 cm wide, while its peduncle reaches 187 cm in length. The tunic is white, almost transparent, through which body muscles can be seen. After formalin preservation it turns yellowish. It has a smooth appearance, although it is completely covered by tiny vesicles with pointy tips arranged somewhat away from each other (Fig. 7B). The postero-ventral crest is T-shaped: it consists of 3 continuous lamellae that end halfway along the body. The two lamellae that encircle the atrial aperture are interrupted at the dorsal region, failing to form a complete circle. The remaining third lamella runs through the mid-ventral line of the body. The oral siphon is situated at a short distance from the peduncle. The atrial siphon, situated posteriorly, is large. In the bigger specimen it measures 2 cm in diameter. A total of 34 oral tentacles of three different sizes are disposed in a circle. They have ramifications of three orders. The oral tentacle located over the dorsal region is the biggest. The pre-pharyngeal band is at a short distance from the oral aperture. It is composed of two smooth lamellae and makes a marked V around a prominent “C”-shaped dorsal tubercle. The dorsal lamina, composed of separate triangular languets, extends from the border of the dorsal tubercle until the entrance of the esophagus. In the biggest specimen, we counted 55 languets. Strong longitudinal muscle fibers intercalate with strong transverse muscle fibers, forming a mesh. Thinner circular fibers are disposed around both siphons. There are six folds on each side of the branchial sac. The branchial formula for the left side of the biggest specimen is: DL -7 (10) 6 (10) 8 (6) 10 (7) 7 (5) 5 (5) 8- E The gut makes an open loop. The stomach is covered by two rows of hepatic diverticula. There is a wide atrial velum, with curved borders. The anal boder is smooth. Each gonad consists of a compact globular mass composed of numerous testicular follicles distributed over a short ovary. Both structures are embedded in a big endocarp. The gonads do not present lobes. There are three gonads on each side of the body. On the left side, the most ventral gonad is small and located in the gut-loop. The remaining two are located almost parallel to the intestine. On the right side, two gonads run almost parallel to the endostyle, one under the other. The remaining gonad, bigger in size, is located dorsally (Fig. 7C). Stomach contents. No remains of prey items were found. Remarks. This is the third record of Culeolus likae , increasing to seven the total number of specimens recorded. The geographic and bathymetric ranges of the species are extended, being the present the southern and shallowest register. The smaller specimen studied lacks part of the branchial sac, digestive system and gonads. Only the musculature, neural system, oral tentacles and dorsal lamina are intact. Notwithstanding, the external aspect is identical to the description for the species provided by Sanamyan K. & Sanamyan N. (2002). The larger specimen presents a peduncle which is 1 m longer than the longitude reported by the latter authors for the biggest specimen they collected (the holotype). Even though the position and the structure of the gonads may vary in some species of Culeolus , our intact specimen has the same position and shape of the one provided by Sanamyan K. & Samanyan N. (2002) for the holotype of C. likae . The differences found are: a higher number of oral tentacles (34 in our specimen; 20 in the holotype), the shape of the dorsal tubercle (“S”-shaped instead of “C”-shaped) and the border of the anus (with two lobes instead of smooth). The difference in the number of oral tentacles could be due to the difference in size of the individuals compared. The shape of the dorsal tubercle is variable in numerous ascidian species; thus, we do not consider it a reliable character in the case of species diagnosis. The difference in the border of the anus might be attributed to incomplete fixation. : Published as part of Maggioni, Tamara, Rimondino, Clara, Taverna, Anabela, Reyna, Paola, Lagger, Cristian, Alurralde, Gastón, Calcagno, Emilia & Tatián, Marcos, 2022, Abyssal ascidians (Chordata, Tunicata) from the Weddell Sea, Antarctica, including a new Styela species and stomach content identifications, pp. 296-314 in Zootaxa 5093 (3) on pages 307-308, DOI: 10.11646/zootaxa.5093.3.2, http://zenodo.org/record/5909824